The Effect of Feed Supplement Balance on the Nutritional and Mineral Content of Rice Bran Fermented with Bacillus amyloliquefaciens - Yolani Utami; Wizna; Yose Rizal (Andalasian Livestock, 2024)
This research aims to determine the balanced effect of feed supplements on the nutritional and mineral content of rice fermented with Bacillus amyloliquefaciens. The research used a completely randomized design with a 3 x 3 x 3 factorial pattern with three replications for each treatment combination. The treatment factors consist of factor I, three levels of Zn (25, 50, 75 ppm); factor II, three levels of urea (1.0, 1.5, 2.0%); and factor III, three levels of sulfur (0.2, 0.4, 0.8%). The research results showed that treatment A (Zn), factor B (Urea) had a very significant effect (P<0.01) and factor C (sulfur) had a non-significant effect (P>0.05). Treatment of factors A (Zn) and B (urea) had a significantly different effect (P<0.05) on calcium content. Factor C (sulfur) had no significant effect (P>0.05), and there was no interaction between treatment factors. Treatment of factor A (Zink), factor B (urea), and factor C (sulfur) had no significant effect (P>0.05). There is an interaction between the AC factor (Zn and sulfur), while there is no interaction between the AB factor (Zn and urea), the BC factor (urea and sulfur), and the ABC factor (Zn, urea and sulfur). It can be concluded that the administration of 25 ppm Zn, 2% urea, and 0.2% sulfur gave the best results on the crude protein content (22.62%), calcium (0.33%), and phosphorus (1.22%) of fermented rice bran with Bacillus amyloliquefaciens.